Orthopedic taping, wrapping, bracing & padding - Beam, Joel W. 1963- (F.A. Davis, 2012)
Master the art and science of taping, wrapping, bracing, and padding techniques for the prevention, treatment, and rehabilitation of common athletic injuries and conditions